THE REALIZATION OF POLITENESS IN “A DOLL’S HOUSE” SCRIPT - Ajar Pradika Ananta Tur (Universitas Islam Sultan Agung, 2016)
Politeness is considered to be important in the communication. When thepeople are communicating to one another, they are expected to keep thesocial relationship and do not violate another face or called as facethreatening acts (FTAs). This research investigated the realization ofpoliteness in a drama script entitled “A Doll’s House” by Henrik Ibsen. Itaims to classify the drama conversation parts into some categorizations ofpoliteness and to analyze why they differ in the context. In its nature, theresearch applied qualitative concepts. Two conversation parts in the firstact of the script were chosen to be the objects of the research. Thesequalitative data were then analyzed and categorized using Goffman’scategorizations of Face Threatening Act (FTA): FTA off record and FTA onrecord (with sub-classes: FTA on-baldly, FTA on record-with negativepoliteness, and FTA on record-with positive politeness). From the analyses,it was concluded that there were some parts belonging to FTA off recordand some belonging to the FTA on record with positive politeness. The firstdata analysis explained much about FTA off record. On the contrary, FTAon record with positive politeness was portrayed in the second analysis. Itshows that people tend to save their inter-interlocutors’ face by usingindirect request, off record, as far as they understand what the speakerswant to. The on record will work if only the first one does not work.Keywords: Politeness, FTA off-record, FTA-on record